Developments with hybrid-Trefftz stress and displacement elements - Teixeira de Freitas, João A.; Cismaşiu, Corneliu (Computer Assisted Methods in Engineering and Science, 2001)
The paper reports on the work on hybrid-Trefftz finite elements developed by the Structural Analysis Research Group, ICIST, Technical University of Lisbon. A dynamic elastoplastic problem is used to describe the technique used to establish the alternative stress and displacement models of the hybridTrefftz finite element formulations. They are derived using independent time, space and finite element bases, so that the resulting solving systems are symmetric, sparse, naturally p-adaptive and particularly well suited to parallel processing. The performance of the hybrid-Trefftz stress and displacement models is illustrated with a number of representative static and dynamic applications of elastic and elastoplastic structural problems.